Terraform cookbooks : provision, run, and scale cloud architecture with real-world examples using Terraform - Krief, Mikael; Dadgar, Armon (Expert insight., 2023)
HashiCorp Configuration Language (HCL) has changed how we define and provision data center infrastructure with the launch of Terraform, a top-tier product for building Infrastructure as Code (IaC). Terraform Cookbook shows you how to leverage Terraform to manage complex infrastructure with ease. This new edition has been updated to include real-world examples for provisioning Azure, AWS and GCP infrastructure with Terraform. You'll delve into manual and automated testing with Terraform configurations, creating and managing a balanced, efficient, and reusable infrastructure with Terraform modules. You'll learn how to automate the deployment of Terraform configuration with continuous integration and continuous delivery (CI/CD). Besides that, several new chapters have been added that describe the use of Terraform for Docker and Kubernetes, examine advanced topics on GitOps practices, and explain how to test Terraform configurations using different tools to check code and security compliance. The final chapter covers troubleshooting common Terraform issues and provides solutions for frequently encountered errors. By the end of this book, you'll have developed the skills needed to get the most value out of Terraform and to effectively manage your infrastructure.